EFFORTS OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN IMPROVING THE CRITICAL THINKING SKILLS OF LEARNERS AT MTS BABUL ULUM PAJAK RAMBE MEDAN LABUHAN - Suhendri Suhendri; Eliza Afrina (Almufida : Jurnal Ilmu-Ilmu Keislaman, 2021)
The results achieved in improving the critical thinking skills of learners in Babul Ulum MTs are: (1) achieved of course they understand every material conveyed so that from what they understand can be applied in everyday life. (2) Learners have often read (3) learners are more responsive than a problem when learners are able to think critically (4) more responsive to problems are not sharper analysis of a problem or problem.